Impact analysis of inclusion complexation on micromeritic properties and dissolution behavior of carvedilol - Khandaker Sagir Ahmed, Md. Abdullah Al Masum, Sabiha Sultana, Mohiuddin Ahmed Bhuiyan, Md. Selim Reza (Journal of Applied Pharmaceutical Science, 2016)
The study aimed at investigating an inclusion complexation technique to improve solubility and dissolution characteristics of carvedilol by successful complexation with β-cyclodextrin. Inclusion complexes (ICs) of drug and β-cyclodextrin were prepared by kneading method in four different ratios. Physical mixtures were also prepared in identical ratios to compare the efficacy of prepared ICs. The preparations were subjected to rheological studies, drug loading, in vitro release study, FT-IR spectroscopy, thermal events analysis by DSC, X-ray diffraction, scanning electron microscopy (SEM) and accelerated stability study. IC granules were free flowing and compressible. FT-IR study denoted to absence of any chemical interactions between drug and carrier. DSC and X-ray diffraction suggested the presence of crystalline drug in the complexes. Dissolution of ICs revealed significant enhancement of release rate and extent compared to untreated drug. MDT, %DE and T25%, T50% and T80% indicated marked improvement in release rate from complexes. Kinetic modeling suggested that fickian diffusion was the predominant mechanism of drug release from solid complexes. Stability samples showed no significant alterations in DSC and FT-IR studies that referred to the stability of ICs. ICs were compatible, effective and stable over time. Further studies can be planned to investigate their therapeutic efficacy.
Keywords: Complexation, carvedilol, cyclodextrin, crystallinity and kinetic modeling.